Plastome Data of Red Currant and Gooseberry Reveal Potential Taxonomical Issues within the Ribes Genus (Grossulariaceae) - Anna Pikunova; Svetlana Goryunova; Olga Golyaeva; Maria Dolzhikova; Anna Pavlenko; Oleg Kurashev; Evgeniia Sotnikova; Oksana Polivanova; Anastasia Sivolapova; Oleg Kazakov; Denis Goryunov (Horticulturae, 2023)
The complete chloroplast genomes of red currant cultivar ‘Belaya Potapenko’ and gooseberry cultivar ‘Nekrasovskij’ were sequenced and assembled for the first time. The plastomes are 157,802 bp and 157,559 bp in length for Ribes rubrum and R. uva-crispa, respectively. The R. rubrum cp genome is 243 b.p. longer. It has one more protein-coding gene ycf1, which is pseudogenized in the R. uva-crispa cp genome. In total, 56 and 54 simple sequence repeats (SSRs) were identified within the assembled plastid genomes. The SSR content of plastid genomes was assessed for the 18 Saxifragales species. Phylogeny inference based on plastome data of 18 Saxifragales revealed that all Ribes species are clustered together on the phylogenetic tree, though R. fasciculatum seems to be the most distant from the other analyzed Ribes species. The position of taxa inside the Ribes genus clade does not support the concept of its division into five subgenera. All Ribes species share approximately the same set of protein-coding genes in their plastome sequences. There was multiple independent pseudogenization of the ycf1 gene within the Ribes genus as well as other Saxifragales taxa. Negative selection was observed for most of the genes in both the Ribes group and Saxifragales. A positive selection ratio was observed only inside the Ribes group for the ycf4 and clpP genes. Together with positive selection signatures, pseudogenization events of ycfs genes perhaps reflect that these genes’ evolution was important for Ribes’ adaptation. Thus, our study provides genomic resources and valuable reference for marker development, and makes some clarifications of the phylogenomics of the Ribes genus.